Internet and society in Latin America and the Caribbean - Cliche, Gilles; Bonilla, Marcelo (International Development Research Centre, 2004)
This book presents pioneering research that is designed to show, from a qualitative and ethnographic perspective, how new information and communication technologies, as applied to the school system and to local governance initiatives, merely reproduce traditional pedagogical approaches and the dominant forms by which power is exercised at the local level. The studies thus constitute points of departure for further thinking about the need to promote an Internet culture based on the social application of a "right to communication and culture" and an "Internet right," that will permit the establi.